Electricity market operation: Transitioning from a free market to a single buyer structure - Toby Daglish; Gabriel Godofredo Fiuza de Bragança; Sally Owen; Teresa Romano (Institute for Applied Economic Research (ipea), 2016)
We examine electricity market reform in Brazil: from the 1990s till 2004 the largely hydro-powered market cleared using a market mechanism, and in March 2004 reformed to a single buyer structure. We model monthly log price differences using a two-state Markov Switching model, allowing water storage and natural inflows to affect both the mean and volatility of changes. Our results suggest that the single buyer structure decreased volatility during stable periods but worsened energy crises. Post-reform, we find that the market is safe from crises for a wider range of stored water/rainfall combinations; however the steady state levels of these variables can lead to energy crises developing.
Keywords: C5; L51; L94; 330; regulatory economics; electricity price; risk; wholesale market; Markov Switching model